Application of numerical methods to determine some parameters of radiation embrittlement of borosilicate glass - Kazhykenov, Sh.M.; Yerbolatova, G.U.; Tussupbekova, A.K. («Академик Е.А. Бөкетов атындағы Қарағанды ұлттық зерттеу университеті» КеАҚ, 2025)
In this paper, a numerical method for determining the parameters of radiation embrittlement in borosilicate glass is proposed. The method is based on analyzing the changes in the mechanical properties of the material under radiation exposure, using known irradiation parameters: the total interaction cross section 𝜎tot of glass atoms, the fluence Ф and the energy E of protons. To quantitatively assess the accumulated damage, the DPA (displacements per atom) model is used, and numerical calculations are performed in LAMMPS (molecular dynamics) and COMSOL (analysis of mechanical properties). The obtained results allow us to predict structural changes in glass and to design materials with enhanced resistance to radiation damage. The particle energy range of 1–10 MeV is considered, a correlation is established between radiation defects and a decrease in the elastic modulus. The threshold value of radiation damage (DPAcr), the change in the elastic modulus and the ultimate strength of glass depending on the radiation dose were determined. The effective elastic modulus after irradiation was calculated, which quantitatively describes the change in the material properties. It was determined at what fluence value the critical destruction of the glass structure begins.
Боросиликатты шынының радиациялық сынғыштығының кейбір параметрлерін анықтау үшін сандық әдістерді қолдану
Применение численных методов для определения некоторых параметров радиационного охрупчивания боросиликатного стекла
Keywords: radiation embrittlement; total interaction cross section; DPA; elastic modulus; radiation resistance; nuclear materials; modeling